POTENSI RUMPUT-RUMPUTAN UNTUK FITOREMEDIASI LAHAN TERDEGRADASI PENAMBANGAN EMAS - Fauzia Syarif; Titi Juhaeti (BERITA BIOLOGI, 2003)
Phytoremediation is defined as a clean up of pollutants primarily mediated by pliotosynthetic plants so its could be used as an alternative technique to overcome contaminated soil and water such an mining ecosystems. These plants have several beneficial characteristics; they have ability to accumulate metals in their shoots and especially high tolerance to heavy metals.Since Indonesia has abundant plant diversity, it is believed that some of them are potential to be used as phytoremediator.This research was carried out to study the potential of three species of grasses in accumulating Pb and Cn. The treatments were arranged on Randomized Complete Block Design (factorial design). The first treatment are species of grass: 1) Cynodon dactylon Pers., 2)Cyperus sp. and 3) Ischaemum timorense Kith.; the second treatment is planting media i.e. 1) tailing soil, 2) soil from wildmining (mining activities run by unexpected miners) and 3) top soil and the third is organic fertilizer: 1) manure, 2) compost and 3) no fertilizer.The resultsshowed that all of the three grasses are potential to accumulate Pb and Cn. Organic fertilizer mixed on planting media is significantly affected the growth of grasses and increasing the accumulation of Cn on leaf of Cyperus sp. and I.timorense. While no evidence in increasing Pb accumulation on all of those three grasses species